PENGARUH MEDIA PEMBELAJARAN L-BOND TERHADAP KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR - Nilam Nur Amalia; Agus Kamaludin (JURNAL PENDIDIKAN SAINS (JPS), 2019)
The purpose of this research was to examine the effect of using L-Bond learning media on critical thinking skills and students’ learning outcomes on chemical bonding material. The research was conducted in State Senior High School 5 Yogyakarta, on 10th grade of mathematics and natural sciences, in the academic year of 2017/2018. The type of research was quasi-experiment with the research design of Non-equivalent Control Group Design. The sampling technique was a simple random sampling. The data collection instruments included pre-test until post-test, critical thinking skill test, observation sheet, and student response sheet. The research also carried out an analysis of the stages of students' critical thinking skill, those are clarification, assessment, inference, and strategy. Based on statistical tests, the results showed that the use of L-Bond learning media had an effect on students' critical thinking skills. However, it did not affect students’ learning outcomes. Even so, both the experimental class and the control class showed that the students’ learning outcomes was above the average of completeness criteria 70.